2022
DOI: 10.1371/journal.pone.0263777
|View full text |Cite
|
Sign up to set email alerts
|

Community correlates of change: A mixed-effects assessment of shooting dynamics during COVID-19

Abstract: This study examines changes in gun violence at the census tract level in Philadelphia, PA before and after the onset of the COVID-19 pandemic. Piecewise generalized linear mixed effects models are used to test the relative impacts of social-structural and demographic factors, police activity, the presence of and proximity to drug markets, and physical incivilities on shooting changes between 2017 and June, 2021. Model results revealed that neighborhood structural characteristics like concentrated disadvantage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Our findings indicate the importance of the spatial clustering of drug overdose and firearm injury, and it is plausible the high rates of drug overdose are associated with the illicit drug market. This notion aligns with prior research that finds proximity to drug markets, and drug market activities are associated with higher rates of shootings following the onset of the COVID-19 pandemic (Johnson and Roman 2022 ). Research also demonstrates a perceived need to have a firearm for self-protection in stateless markets (Donohue and Levitt 1998 ), and co-existing risk factors among opioid users and firearm injuries exist (Stein et al 2018 ; Pontes and Pontes 2021 ) therefore increasing the chance for firearm injury.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings indicate the importance of the spatial clustering of drug overdose and firearm injury, and it is plausible the high rates of drug overdose are associated with the illicit drug market. This notion aligns with prior research that finds proximity to drug markets, and drug market activities are associated with higher rates of shootings following the onset of the COVID-19 pandemic (Johnson and Roman 2022 ). Research also demonstrates a perceived need to have a firearm for self-protection in stateless markets (Donohue and Levitt 1998 ), and co-existing risk factors among opioid users and firearm injuries exist (Stein et al 2018 ; Pontes and Pontes 2021 ) therefore increasing the chance for firearm injury.…”
Section: Discussionsupporting
confidence: 87%
“…Emergency management services (EMS) activity was also included in the analyses. EMS activity was defined as all dispatch runs excluding overdoses, and the EMS activity measure was included as a z -score (Johnson and Roman 2022 ). A spatially lagged variable on the dependent variable was included to account for positive spatial autocorrelation.…”
Section: Methodsmentioning
confidence: 99%
“…If broadscale deprosecution of felonies and misdemeanors is leading to a large increase in homicides, particularly murders of the most disadvantaged citizens in American cities, then the appropriate reform position is to moderate such de-prosecution policies, as suggested in the De-Prosecution Article. The emerging consensus is that the correct balance may be for prosecutors to consider lighter sentences and diversion for first-time, non-violent misdemeanors offenses (Agan et al, 2021), while maintaining vigorous prosecutions for violence-related felonies (Hogan, 2022;Johnson & Roman, 2022;Neil & MacDonald, 2022). The Response worries that the De-Prosecution Article promotes "false narratives" and is "a real threat to evidence-based public safety interventions."…”
Section: Discussionmentioning
confidence: 99%
“…Johnson and Roman (2022) examined the impact of Covid‐19 on shooting dynamics in the Kensington neighborhood of Philadelphia. The study found that the proliferation of drug markets associated with the pandemic was structurally and causally related to a measurable increase in shooting rates in the neighborhood, noting that “disrupting drug organizations, or otherwise curbing violence stemming from drug markets, may go a long way toward quelling citywide increases in gun violence.” The conclusion from Johnson and Roman (2022) about the necessity of disrupting drug organizations in order to quell gun violence is equally applicable to the impact of the Philadelphia DAO de‐prosecuting drug trafficking crimes from 2015 to 2019. Piza and Connealy (2022) studied the effect of a police‐free zone established in Seattle during George Floyd‐related protests in 2020.…”
Section: Updated Parallel Research and Real‐world Observationsmentioning
confidence: 99%
“…To break the simultaneity of police and crime, which is often ignored in this line of study (e.g., Johnson & Roman, 2022), we establish the extent to which policing deviated from the status quo in Denver neighborhoods. We do this by generating 3-week rolling average deviations in policing from the same 3-week rolling average in (weighted) 2016-2019.…”
Section: Police Discretionary Behaviorsmentioning
confidence: 99%